Migration, remittances and educational outcomes: The case of Haiti - Sebastian Bredl (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2009)
Using the Cox proportional hazards model this paper empirically investigates how migration of household members and the receipt of remittances affect educational outcomes in Haiti. Based on a theoretical approach it tries to disentangle the effects of both phenomena that have mostly been jointly modeled in previous literature. The results suggest that remittances play an important role for poor households in alleviating budget constraints, whereas no effect of the migrated household head's absence is detected. The latter might be so due to the high imprecision surrounding the estimated hazard ratios. Household wealth, captured via an asset index, is found to have a signi?cant impact on education as well, supporting the idea that budget constraints play a crucial role in schooling decisions in Haiti due to the dominance of private schools and the high poverty rate in the country.
Keywords: F24; J24; O15; 330; Haiti; education; remittances; migration; Bildungsverhalten; Bildungsfinanzierung; Rücküberweisung (Migranten); Internationale Wanderung; Privater Haushalt; Budgetrestriktion; Armut; Haiti